ANALISIS DAN PERANCANGAN APLIKASI PENGATUR POLA HIDUP SEHAT BERBASIS ANDROID - Wisnumurti Wisnumurti; Novi Lestari (Jurnal Informatika dan Komputer (JIK), 2018)
Current technological developments are increasingly rapid, with the development of technology, especially internet networks that can provide benefits to users. In the era of globalization the development of this technology directly and indirectly makes changes in people's lifestyle become more practical, effective and efficient. Many fast food such as fast food or junk food are available everywhere. Fast food and lifestyle changes cause unhealthy eating patterns, which can cause health problems related to nutrition. Malnutrition is a health problem related to nutrition that cannot be addressed. With an appropriate healthy lifestyle will help to be healthier and away from disease. World progress such as in developing countries causes many changes in the pattern of human life. Especially nowadays there are many fast or instant foods. The busyness faced by everyone causes them to ignore their lifestyle so that many diseases can attack them at any time. This study uses research methods, namely 1). Primary data in the form of observations carried out in the hospital of Siti Aisyah Lubuklinggau, addressed at Lapter Silampari Street, Kuti Lubuklinggau Timur Village, I 31626, Documentation. 2) Secondary data is data obtained by researchers from various existing sources. Secondary data is obtained from various sources including books, journals, reports and others. This application was built with 1). Designing healthy lifestyle applications using eclipse, System design design uses UML (Unified Modeling Language) and system testing using black box method, 2). Designing android-based healthy lifestyle management applications to make it more effective and efficient, and help the community about lifestyle rules healthy. With this application, it is expected to help the community in implementing and regulating a good and right healthy way of life